Finite element analysis of biomechanical effects of mineralized collagen modified bone cement on adjacent vertebral body after vertebroplasty - Yang, Cunheng; Wang, Fumin; Huang, Xingxing; Zhang, Hao; Zhang, Meng; Gao, Junxiao; Shi, Shengbo; Wang, Fuyang; Yang, Fangjun; Yu, Xiaobing (Frontiers in Bioengineering and Biotechnology, 2023)
Objective: To investigate whether mineralized collagen modified polymethyl methacrylate (MC-PMMA) bone cement impacts the implanted vertebral body and adjacent segments and the feasibility of biomechanical properties compared with common bone cement in the treatment of osteoporotic vertebral compression fractures (OVCF). Methods: A healthy volunteer was selected to perform a three-dimensional reconstruction of the T11-L1 vertebral body to establish the corresponding finite element model of the spine, and the changes in the stress distribution of different types of cement were biomechanically analyzed in groups by applying quantitative loads. Results: The stress distribution of the T11-L1 vertebral body was similar between the two bone types of cement under various stress conditions. Conclusion: Mineralized collagen modified bone cement had the advantages of promoting bone regeneration, good biocompatibility, good transformability, and coupling, and had support strength not inferior to common PMMA bone cement, indicating it has good development prospects and potential.